2021
DOI: 10.1037/abn0000552
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptom dimensions and brain responses to startling auditory stimuli in combat veterans.

Abstract: Posttraumatic stress disorder (PTSD) is marked by alterations in emotional functioning, physiological reactivity, and attention. Neural reactivity to acoustic startle stimuli can be used to understand brain functions related to these alterations. Investigations of startle reactivity in PTSD have yielded inconsistent findings, which may reflect the heterogeneity of the disorder. Furthermore, little is known of how the common cooccurrence of mild traumatic brain injury (mTBI; i.e., concussion) may influence neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Our primary intention in the current report was to investigate if beta burst events could index response control dysfunction related to posttraumatic stress symptomatology in combat-exposed veterans. In line with prior reports of brain activation in combat-exposed veterans (Marquardt et al, 2021), we found that BBR predicted PTSD symptom severity but failed to be associated with a categorical diagnosis of PTSD. It is possible that the association with symptoms merely reflects an increase in statistical power with continuous as opposed to dichotomous measures (Altman & Royston, 2006; Lazic, 2008); however, the benefit of dimensional measures mirrors a recent focus on less reliance on diagnostic categories in psychopathology research.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our primary intention in the current report was to investigate if beta burst events could index response control dysfunction related to posttraumatic stress symptomatology in combat-exposed veterans. In line with prior reports of brain activation in combat-exposed veterans (Marquardt et al, 2021), we found that BBR predicted PTSD symptom severity but failed to be associated with a categorical diagnosis of PTSD. It is possible that the association with symptoms merely reflects an increase in statistical power with continuous as opposed to dichotomous measures (Altman & Royston, 2006; Lazic, 2008); however, the benefit of dimensional measures mirrors a recent focus on less reliance on diagnostic categories in psychopathology research.…”
Section: Discussionsupporting
confidence: 90%
“…For example, the DSM-5 (2013) includes severity indicators for many disorders, consistent with the critical role that disorder severity plays in clinical management. The lack of an association of BBR with mTBI adds to the growing body of evidence that many reported consequences of military mTBI can be attributed to psychopathology other than mTBI, including PTSD (Disner et al, 2017; Marquardt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus if there is greater noise in the single‐trial mean amplitude measurements (i.e., a larger standard deviation), the SME will be larger, indicating lower precision in single‐trial mean amplitudes. Finally, much ERP research seeks to examine the relationship of brain potentials with individual differences (Dong et al, 2015; Marquardt et al, 2021), which requires reliable ERP measures (though see: Hedge et al, 2018). As discussed in Luck et al (2020), classical reliability is sensitive to the degree of heterogeneity in a given sample such that greater heterogeneity leads to greater reliability estimates even when the precision of the measurement (e.g., SME) is held constant.…”
Section: Introductionmentioning
confidence: 99%
“…An exclusive focus on categorical definitions of PTSD may obscure which symptom domains are predictive of functional outcomes and limit statistical power for detecting associations with cognitive mechanisms (Cuthbert, 2005;Grove, 1991). Factor analyses suggest the existence of separate PTSD symptom dimensions: intrusive reexperiencing, avoidance, dysphoric mood, and hyperarousal (Yufik & Simms, 2010), which appear to more closely track with brain-based systems than the PTSD diagnosis alone (Lieberman et al, 2017;Marquardt et al, 2018Marquardt et al, , 2021. Therefore, investigating how specific symptom dimensions of PTSD map onto memory deficits may clarify what aspects of the disorder relate to the consolidation and retrieval of verbal material.…”
mentioning
confidence: 99%